Optimasi Pengambilan Antosianin dari Kulit Buah Naga Merah (Hylocereus polyrhizus) Sebagai Pewarna Alami pada Makanan - Ratna Sri Harjanti (CHEMICA: Jurnal Teknik Kimia, 2016)
The addition of synthetic colors in foods in an attempt to attract the attention of consumers, not a ban, but if the dye used is a dye that is unusual for the food, it is harmful to health. One source of natural pigments that can be used is the red dragon fruit skin. These skins contain anthocyanins potential as a dye.             In this reasearch, the observed red dragon fruit skin moisture content and size of the powder. It also conducted a stirring speed variation during the extraction process. While variable temperature, time, and solvent refers to the optimum conditions of research that has been done. Analysis of the results was conducted to determine pH, anthocyanin concentration and yield results.             Based on the results obtained, the smaller the water content contained in the skin, giving absorbance values are higher. This shows that extractable anthocyanins levels are also higher. The lowest levels of the skin can be achieved in this study was 6%. The smaller the grain size, the higher the anthocyanin content. The smallest grain size achieved was 100 mesh. The highest mixing speed in this study was 300 rpm, the higher the stirring speed, the higher the anthocyanin content fetched.             Organoleptic tests were conducted to study the effect of anthocyanins on the quality of the food shows that the addition of anthocyanins provide the appropriate color and do not significantly affect flavor and aroma. So it can be used as a natural dye for food.